Cross-sectional study of workplace violence on work engagement among Chinese nurses: the mediating role of psychological resilience - Miao Chen; Xiaoli Liao; Hao Xie (BMJ Open)
Objectives This study aimed to investigate the status of workplace violence, psychological resilience and work engagement, and explore the potential mediating role of psychological resilience in the relationship between workplace violence and work engagement among Chinese nurses.Design A cross-sectional survey was conducted among a convenience sample of clinical registered nurses.Setting A convenience sample of clinical registered nurses was recruited from affiliated hospitals of Hunan University of Chinese Medicine.Participants A total of 1725 questionnaires were received, of which 1571 were deemed valid, resulting in an effective response rate of 91.07%. The final sample consisted of 1571 clinical registered nurses with a mean age of 31.65±7.16 years.Outcome measures Data were collected through an online questionnaire comprising a general information form, the Workplace Violence Scale (WVS), Connor-Davidson Resilience Scale (CD-RS) and Utrecht Work Engagement Scale (UWES). Descriptive analysis, correlation analysis, and mediation analysis were performed using IBM SPSS Statistics software.Results This cross-sectional investigation recruited a convenience sample of 1571 clinical registered nurses, who encountered multiple types of workplace violence in the past year. Pearson correlation analysis indicated negative associations between workplace violence and work engagement (r=−0.505, p<0.01), as well as between workplace violence and psychological resilience (r=−0.523, p<0.01). Mediation analysis revealed that psychological resilience partially mediated the relationship between workplace violence and work engagement, with the mediation effect accounting for 66.67% of the total effect.Conclusions Nurses exposed to workplace violence demonstrated decreased work engagement, while psychological resilience acted as a protective factor to mitigate the adverse impacts of workplace violence on work engagement. These findings provide a theoretical basis for interventions that equip nurses with resilience to combat workplace violence and improve work engagement.